Monocytes/macrophages prevent healing defects and left ventricular thrombus formation after myocardial infarction. Issue 3 (16th November 2012) - Frantz, Stefan; Hofmann, Ulrich; Fraccarollo, Daniela; Schäfer, Andreas; Kranepuhl, Stefanie; Hagedorn, Ina; Nieswandt, Bernhard; Nahrendorf, Matthias; Wagner, Helga; Bayer, Barbara; Pachel, Christina; Schön, Michael P.; et al.
Abstract : Myocardial infarction (MI) leads to rapid necrosis of cardiac myocytes. To achieve tissue integrity and function, inflammatory cells are activated, including monocytes/macrophages. However, the effect of monocyte/macrophage recruitment after MI remains poorly defined. After experimental MI, monocytes and macrophages were depleted through serial injections of clodronate‐containing liposomes. Monocyte/macrophage infiltration was reduced in the myocardium after MI by active treatment. Mortality was increased due to thromboembolic events in monocyte‐ and macrophage‐depleted animals (92 vs. 33%; P <0.01). Left ventricular thrombi were detectable as early as 24 h after MI; this was reproduced in a genetic model of monocyte/macrophage ablation. A general prothrombotic state, increased infarct expansion, and deficient neovascularization were not observed. Severely compromised extracellular matrix remodeling (collagen I, placebo liposome vs. clodronate liposome, 2.4±0.2 vs. 0.8±0.2 arbitrary units; P <0.001) and locally lost integrity of the endocardium after MI are potential mechanisms. Patients with a left ventricular thrombus had a relative decrease of CD14 + CD16 + monocyte/macrophage subsets in the peripheral blood after MI (no thrombus vs. thrombus, 14.2±0.9 vs. 7.80±0.4%; P <0.05). In summary, monocytes/macrophages are of central importance for healing after MI. Impaired monocyte/macrophage function appears to be an unrecognized new pathophysiological mechanism for left ventricular thrombus development after MI.—Frantz, S., Hofmann, U., Fraccarollo, D., Schäfer, A., Kranepuhl, S., Hagedorn, I., Nieswandt, B., Nahrendorf, M., Wagner, H., Bayer, B., Pachel, C., Schön, M.P., Kneitz, S., Bobinger, T., Weidemann, F., Ertl, G., Bauersachs, J. Monocytes/macrophages prevent healing defects and left ventricular thrombus formation after myocardial infarction. FASEB J. 27, 871–881 (2013). www.fasebj.org